The Influence of Wealth, Intergovernmental Revenue, Economic Growth, and Audit Opinion BPK on the Financial Performance of Regency/City Governments in Jambi Province for the Period 2020–2023 - Lubis, Daniel Siswanto; Sam, Iskandar; Silvera, Dica Lady (Jurnal Cakrawala Akuntansi, 2025)
This study aims to examine the effect of Wealth, Intergovernmental Revenue, Economic Growth, and BPK Audit Opinion on the Financial Performance of Regency/City Governments in Jambi Province for the period 2020–2023. This research employs a quantitative approach using secondary data obtained from the Audit Board of the Republic of Indonesia (BPK) Representative Office in Jambi Province and the Central Bureau of Statistics of Jambi Province. Data were collected through documentation and processed using SPSS version 30. The results show that Wealth, Intergovernmental Revenue, Economic Growth, and BPK Audit Opinion simultaneously affect the financial performance of local governments. Partially, Wealth has a significant positive effect, while Intergovernmental Revenue has a significant negative effect. Meanwhile, Economic Growth and BPK Audit Opinion have no significant impact. These findings imply that local governments should focus on enhancing the management of regional assets to improve financial performance and reduce dependency on intergovernmental transfers to strengthen fiscal independence and effectiveness. Additionally, the lack of significant influence from Economic Growth and Audit Opinion indicates that macroeconomic indicators and audit outcomes alone may not be sufficient drivers of financial performance without strong internal financial governance